ANALISIS PENDAPATAN USAHATANI PADI ANGGOTA GAPOKTAN WIDODO DESA NGEMBALREJO KECAMATAN BAE KABUPATEN KUDUS - Nadia Soraya Esfandiari; Migie Handayani; Kustopo Budiraharjo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The aims of the study was to analyze the income of rice farming who are members of Gapoktan Widodo and analyze the relationship between the independent variables in the form of seed costs, fertilizer costs, pesticide costs, labor expenditure, land area, the amount of production on the dependent variable, namely the income of rice farmers who are members of Gapoktan Widodo in Ngembalrejo Village, District Bae, Kudus Regency. This research was used survey method. Methods of data collection using observation and interviews with questionnaires. The method of determining the sample using the census is as many as 88 rice farmers. Data analysis used descriptive and quantitative analysis, namely income analysis and Pearson correlation analysis. The results showed that the average production cost incurred was Rp 7,714,838.809.00, the average income was Rp 15,721,647.73.00, and the income earned by the rice farmers who were members of Gapoktan Widodo was an average of Rp. 7,745,187.849.00 with an R/C Ratio of 2.038 and an average profitability of 1.03%. The factors of seed costs, fertilizer costs, pesticide costs, labor expenditure, land area, and the amount of production have a significant and very strong relationship or correlation with the income of rice farmers who are members of the Widodo Gapoktan. In addition, these factors also have a direct correlation with the income of rice farmers who are members of Gapoktan Widodo.